2020
DOI: 10.1155/2020/5626481
|View full text |Cite
|
Sign up to set email alerts
|

Hyers–Ulam Stability for Quantum Equations of Euler Type

Abstract: Many applications using discrete dynamics employ either q-difference equations or h-difference equations. In this work, we introduce and study the Hyers–Ulam stability (HUS) of a quantum (q-difference) equation of Euler type. In particular, we show a direct connection between quantum equations of Euler type and h-difference equations of constant step size h with constant coefficients and an arbitrary integer order. For equation orders greater than two, the h-difference results extend first-order and second-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In [4], it has been shown that there is a suitable transformation between the quantum (q and h difference) equations on two different time scales to guarantee stability for both equations. More specifically, it turns out that if the h-difference equation has HUS, then the corresponding quantum equation of Euler type also has HUS.…”
Section: Application To H-difference Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [4], it has been shown that there is a suitable transformation between the quantum (q and h difference) equations on two different time scales to guarantee stability for both equations. More specifically, it turns out that if the h-difference equation has HUS, then the corresponding quantum equation of Euler type also has HUS.…”
Section: Application To H-difference Equationsmentioning
confidence: 99%
“…Under assumption (1.2), they proved the following facts: if λ = 0, then (1. In 2020, the authors [4] introduced a new, direct connection between HUS for h-difference equations and HUS for quantum equations of Euler type. The second purpose of this study is to establish a novel connection between HUS for Cayley quantum equations and HUS for the h-difference equations with a specific variable coefficient, based on the ideas in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…With the attention of many experts and scholars on fractional q-difference, rich results have been achieved on fractional q-difference equations via q-Gronwall equality (see [18]), the existence and stability of the solutions for Riemann-Liouville fractional q-difference equations (see [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]), Caputo fractional q-difference initial boundary value problems (see [34][35][36][37][38][39]). In [40], Boutiara explored the mixed multi-term fractional q-difference equations with q-integral boundary conditions by using topological degree theory.…”
Section: Introductionmentioning
confidence: 99%
“…But the stability of coupled fractional q-difference equations were relatively less explored. In [7,23], the stability of fractional difference about non-autonomous systems and quantum equations of Euler type was discussed, respectively. In [1,2,4,9,13], the existence and finite-time stability of a class of fractional q-difference time-delay systems by the q-Gronwall inequality and the fixed point theorem were studied.…”
Section: Introductionmentioning
confidence: 99%